Geothermal Handbook : Planning and Financing Power Generation - Gehringer, Magnus; Loksha, Victor (World Bank, Washington, DC, 2016)
Developing countries face multiple and complex challenges in securing affordable and reliable energy supplies to support sustainable economic development. These challenges can be addressed by increased access to modern energy infrastructure, enhanced energy security through supply diversification, and transition to low carbon paths to meet rising energy demands. There is broad consensus that renewable energy has a major role to play in addressing these challenges. In recent years, support for renewable energy investment has become a mainstream activity for multilateral development banks and their clients. The World Bank, for instance, has supported geothermal development in Africa, Asia, Europe, and Latin America. Global analytical work and technical assistance on clean energy are also one of the major program areas of the Energy Sector Management Assistance Program (ESMAP). This handbook is dedicated to geothermal energy as a source of electric power for developing countries. Many developing countries are endowed with substantial geothermal resources that could be more actively put to use. On top of the benefits stemming from its renewable nature, geothermal energy has several additional advantages, including the provision of stable and reliable power at a relatively low cost, around the clock, and with few operational or technological risks.